2010
DOI: 10.1016/j.jcrs.2010.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Najjar-Awwad cataract surgery risk score for resident phacoemulsification surgery

Abstract: PURPOSE To validate the Najjar-Awwad cataract surgery risk score for residents, which has been proposed to predict surgical complexity and risk. SETTING Two urban public county hospitals. DESIGN Case series. METHODS Phacoemulsification cataract surgeries performed by residents between January 2005 and April 2008 were retrospectively reviewed. The cataract risk score was calculated retrospectively. Intraoperative complications included posterior and anterior capsular tears, vitreous prolapse, dropped nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
2
18
0
2
Order By: Relevance
“…Cataract cases are usually not as complex at John Peter Smith. In a previous review of 1833 cases, 27 the Najjar-Awwad cataract surgery risk score averaged 6.79 at John Peter Smith and 6.99 at Parkland (P=0.023, unpublished data). While there was a trend towards fewer complications in the second half of the third year of residency when compared to the first half, the difference was not statistically significant (P=0.128).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Cataract cases are usually not as complex at John Peter Smith. In a previous review of 1833 cases, 27 the Najjar-Awwad cataract surgery risk score averaged 6.79 at John Peter Smith and 6.99 at Parkland (P=0.023, unpublished data). While there was a trend towards fewer complications in the second half of the third year of residency when compared to the first half, the difference was not statistically significant (P=0.128).…”
Section: Discussionmentioning
confidence: 88%
“…14 Najjar and Awwad 26 devised a cataract risk score for beginning residents that has recently been validated. 27 These scoring systems were built using a combination of literature search and expert opinion. Many factors in these systems may be superfluous, while others may be missing.…”
Section: Discussionmentioning
confidence: 99%
“…Rutar et al 5 found an increase in complication rates in surgeries performed by residents when there was a dense nuclear sclerotic cataract or zonular weakness. Blomquist et al 8 also found an increased risk for complications among residents performing complex cataract surgery, especially in cases with a dense nuclear sclerotic cataract or a lack of the red reflex. This may point to the need to have, when feasible, an experienced colleague help recent resident graduates in performing complex cataract cases.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies 16,23,31,32 that also excluded patients with preoperative pathology impairing vision have reported visual outcomes of 6/12 or better in 86% to 91% of patients with complications. Overall, only 4 manual SICS patients and 1 phacoemulsification patient experienced intraoperative complications that resulted in a CDVA worse than 6/60 at the 1-month postoperative visit.…”
Section: Discussionmentioning
confidence: 99%